1999
DOI: 10.1104/pp.120.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophyll Cycle Pigment Localization and Dynamics during Exposure to Low Temperatures and Light Stress inVinca major1

Abstract: The distribution of xanthophyll cycle pigments (violaxanthin plus antheraxanthin plus zeaxanthin [VAZ]) among photosynthetic pigment-protein complexes was examined in Vinca major before, during, and subsequent to a photoinhibitory treatment at low temperature. Four pigment-protein complexes were isolated: the core of photosystem (PS) II, the major light-harvesting complex (LHC) protein of PSII (LHCII), the minor light-harvesting proteins (CPs) of PSII (CP29, CP26, and CP24), and PSI with its LHC proteins (PSI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
82
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 43 publications
15
82
0
Order By: Relevance
“…These characteristics are similar to those found in long term overwinter quenching (Verhoeven et al, 1999;Gilmore and Ball, 2000). Previous results demonstrated the existence of a form of sustained (Z ĂŸ A)-dependent energy dissipation, detected in cold-acclimated leaves and retained even upon warming; this mechanism is correlated with slow Z ĂŸ A to violaxanthin conversion and is not associated to nocturnal maintenance of low lumenal pH (Verhoeven et al, 1998).…”
Section: Relation Between Ph-independent and Qe Quenching Typessupporting
confidence: 64%
See 1 more Smart Citation
“…These characteristics are similar to those found in long term overwinter quenching (Verhoeven et al, 1999;Gilmore and Ball, 2000). Previous results demonstrated the existence of a form of sustained (Z ĂŸ A)-dependent energy dissipation, detected in cold-acclimated leaves and retained even upon warming; this mechanism is correlated with slow Z ĂŸ A to violaxanthin conversion and is not associated to nocturnal maintenance of low lumenal pH (Verhoeven et al, 1998).…”
Section: Relation Between Ph-independent and Qe Quenching Typessupporting
confidence: 64%
“…Genetic analysis has identified PsbS as a gene product indispensable for qE, while zeaxanthin and lutein appear as modulators of qE amplitude Pogson et al, 1998). Zeaxanthin accumulation also has been involved in long term (overwinter) downregulation of photosynthesis (Verhoeven et al, 1999;Gilmore and Ball, 2000). Current understanding of energy dissipation suggests that PsbS catalyzes qE upon protonation of lumenal-exposed residues (Li et al, 2002b) and binding of zeaxanthin.…”
Section: Discussionmentioning
confidence: 99%
“…the lipid bilayer of the zea1 chloroplast thylakoids. Previous studies have shown that xanthophylls cycle Car are localized within the minor LHC (Bassi et al, 1993;Verhoeven et al, 1999) and/or may be found as free pigment in the lipid matrix of the thylakoid membrane (Tardy and Havaux, 1996;Bassi and Caffarri, 2000). Relevant in this respect are the findings of Havaux and Niyogi (1999) and Havaux et al (2000), who showed that the npq1 mutant of Arabidopsis, which cannot perform a de-epoxidation of V to Z, is subject to enhanced lipid peroxidation upon photooxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…A peripheral binding site for xanthophyll cycle carotenoids has been identified on LHCII trimers (11,49). This site appears to be only partially occupied, the occupancy increasing under stress conditions when the xanthophyll cycle pool is enlarged (50). Genetic manipulation to increase the pool size similarly leads to increased occupancy of this site (51).…”
Section: Pigment Composition Of Monomeric Lhciimentioning
confidence: 99%